ANALISIS PERAN AKUNTANSI FORENSIK, DATA MINING, CONTINUOUS AUDITING, TERHADAP PENDETEKSIAN FRAUD SERTA DAMPAKNYA PADA PENCEGAHAN FRAUD (STUDI KASUS PADA WATER RESOURCES AND IRIGATION SECTOR MANAGEMENT PROGRAM – DIREKTORAT SUMBER DAYA AIR – KEMENTERIAN PE - Maulidiastuti, Tri; Suratno; Yusuf, Muhammad (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2018)
This research was conducted by distributing questionnaires as the primary data to the Committing Officer (CO) of government institutions who take the program of Water Resources and Irrigation Sector Management Program (WISMP). Those respondents in average already have knowledge of accounting forensics, data mining, continuous auditing , to detect fraud which allegedly was effectively used to prevent fraud. The results of this study are described in the hypothesis testing and continued with the path analysis calculation. Forensic accounting, data mining, continuous auditing variables are able to contribute to the prevention of fraud variable when they are intervened by the fraud detection variable. This conclusion is obtained by calculating the effect of independent variables on the dependent variable that is greater when using the intervening variables (fraud detection).